Analysis of the impact of public-private partnership on the development of the domestic medical industry - I. R. Elistratov (Вестник университета)
The development of the social sphere in the country depends on the development of healthcare and medical industry, which serve as its basis, both at the municipal and regional levels, and show the level of its development. The standard of living and health of the population depend on this sphere. Its qualitative development directly conditioned by the effective model of the healthcare management system, which consists in optimising sources of financing. The study has assessed the most significant pressing problems related to the system and mechanism of financing the healthcare system and medical industry, new possible options for the sources of financing and directions for optimising the distribution of public financing have been explored as well. One of the most effective areas of financing medical institutions at the present stage is public private partnership (hereinafter referred to as PPP). With its help, issues related to modernisation of infrastructure, optimisation of the resource management process in the medical institutions as well as improvement of the level of services provided are addressed. The study also examines risks arising from the use of the PPP in terms of its application as financing for the medical industry and healthcare sector.